Parents' insights after pediatric hospitalization due to rotavirus gastroenteritis in Italy - Federico Marchetti; Volker Vetter; Giorgio Conforti; Susanna Esposito; Paolo Bonanni (Taylor & Francis Group, 2017)
Most of the severe cases of acute gastroenteritis in infants and children under 5 globally are caused by rotavirus infection. There are nearly 15,000 rotavirus gastroenteritis (RVGE) hospitalizations in Italy each year, which could be reduced by available rotavirus vaccines. In addition to the economic and societal burden, RVGE hospitalization could impact families negatively. The aim of this survey was to obtain parents' insights after hospitalization of their child for RVGE. Parents, of 500 children aged 0-5 years, were interviewed about their experience of RVGE hospitalization and asked to rate their stress on different items and overall. Most children (32.6%) were hospitalized aged 12-23 months, and 6.8% were <6 months old. Family pediatricians referred 56.2% of cases to hospital, and 25.8% went based on their parents' decision. During hospitalization, mean parental stress scores (out of 10, with 10 as highest stress) ranged from 6.6 to 8.4. The highest scores were for child malaise (8.42, SD 1.00), vomiting/diarrhea (8.07, SD 0.97), stress for the family in general (7.82, SD 0.90), parental stress (7.68, SD 0.93) and child dehydration (7.18, SD 1.02). The overall stress for the family was graded as 'high' by 67.2% of parents. Geographical areas and stress level were related (p = 0.0071), being the "high" stress score not an evenly distributed variable (p < 0.0001). Most children (91.8%) were not vaccinated against rotavirus, as most parents (74.5%) were not aware of vaccination availability. Parental distress due to RVGE hospitalization appears to be significant (93.6% reporting high/medium stress) and there is an important lack of awareness among parents about rotavirus vaccination. More education on RVGE for families in Italy should be warranted.